Audience Design in Collaborative Dialogue between Teachers and Students. Issue 8 (14th September 2021) - Turner, Christina; Knutsen, Dominique
ABSTRACT: When two people interact, reference presentation is shaped with the intention of supporting addressee understanding, allowing for ease of acceptance, thus minimizing overall collaborative effort. To date, analysis of such audience design has focused largely on adult–adult or adult–child interaction but seldom on adult–teenager interaction, including teacher–student interaction. An experiment was conducted in a British school in which teachers and students interacted to establish a reference for abstract tangram figures. Teachers were able to account for the students' increased ability to behave in a more adult-like collaborative way with dialogue features similar to those in adult–adult contexts. Set apart was dialogue with young students, where teachers continued to guide the interaction by producing lengthier descriptions and by encouraging participation. Dialogue with young students differs from that with other teachers in terms of the amount of effort put into the interaction and in how this effort is distributed and shared among dialogue partners.